Downregulation of RAB7 and Caveolin-1 increases MMP-2 activity in renal tubular epithelial cells under hypoxic conditions - Yu Wenmin (De Gruyter, 2021)
Tubulointerstitial fibrosis leads to tubular basement membrane thickening and accumulation of interstitial extracellular matrix (ECM). Matrix metallopeptidase-2 (MMP-2) is involved in the breakdown of ECM. Chronic hypoxia often occurs in the kidney tissues of patients with chronic kidney disease. Our previous study reported the effect of autophagy and endocytosis on MMP-2 activity in hypoxia-treated HK-2 cells. In this study, the relationship between the Ras-related protein Rab-7a (RAB7) and MMP-2 activity was further investigated. RAB7 overexpression decreased MMP-2 activity. In contrast, the results for RAB7 knockdown displayed the opposite pattern. Short hairpin RNA technology was used to knockdown Caveolin-1 (Cav-1) or Beclin-1 (Bec-1) in HK-2 cells. The two genes displayed differential effects on MMP-2 activity. Cav-1 and RAB7 interference increased MMP-2 activity. This study suggested that autophagy and endocytosis, RAB7, Cav-1, and Bec-1 may serve as potential mediators for altered MMP-2 activity.